Tubulin post-translational modifications and the construction of microtubular organelles in Trypanosoma brucei. - Sasse, R; Gull, K (1988)
We have used specific monoclonal antibodies to facilitate a study of acetylated and tyrosinated alpha-tubulin in the microtubule (MT) arrays in the Trypanosoma brucei cell. Acetylated alpha-tubulin is not solely located in the stable microtubular arrays but is present even in the ephemeral microtubules of the mitotic spindle. Moreover, there is a uniform distribution of this isoform in all arrays. Studies of flagella complexes show that acetylation is concomitant with assembly of MTs. There is no subsequent major modulation in the content of acetylated alpha-tubulin in MTs. Conversely, polymerizing flagellar MTs have a high tyrosinated alpha-tubulin content, which is subsequently reduced to a basal level at a discrete point in the cell cycle. The MTs of the intranuclear mitotic spindle appear never to contain tyrosinated alpha-tubulin, suggesting that they are actually constructed of detyrosinated alpha-tubulin or that detyrosination is extremely rapid at this time in the cell cycle. T. brucei therefore, represents a cell type with extremely active mechanisms for the post-translational modification of alpha-tubulin. Our analyses of the timing of acquisition and modulation in relation to MT construction in T. brucei, suggest that acetylation and detyrosination of alpha-tubulin are two independently regulated post-translational modifications, that are not uniquely associated with particular subsets of MTs of defined lability, position or function. Post-assembly detyrosination of alpha-tubulin may provide a mechanism whereby the cell could discriminate between new and old MTs, during construction of the cytoskeleton through the cell cycle. However, we also suggest that continuation of detyrosination, allows the cell, at cell division, to partition into daughter cells two equivalent sets of cytoskeletal MTs.